2021
DOI: 10.48208/headachemed.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of menstrually-related migraine in a population of students from a municipal university center in the interior of Brazil

Abstract: ObjectiveTo identify the prevalence of migraine associated to menstruation in a population of students at a college in Brazil’s inland.MethodsThe students were recruited and submitted to the Test for the Identification of Women with Menstrual Period-Related Headache based on the ID-MigraineTM and Menstrual Migraine Assessment Tool questionnaires. Migraine diagnosis was made according to ICHD-3 criteria.ResultsOf the 424 students, 312 (73.5%) answered affirmatively in at least two of the four questions in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…28,36 In our findings, definite and probable menstrual-related migraine were 22.5% which is higher than a study conducted in the United Kingdom, and Yugoslavia that reported 7.6%, 37 and 12.6%, 38 respectively. However, studies conducted in Brazil and Spain have reported that the prevalence of MRH among young women was 69.2% and 45.14%, 39,40 respectively. The evidence highlights that MRH was not assessed by a neurologist in this study and was self-reported by the participants, which might have increased the magnitude of MRH in this study.…”
Section: Discussionmentioning
confidence: 97%
“…28,36 In our findings, definite and probable menstrual-related migraine were 22.5% which is higher than a study conducted in the United Kingdom, and Yugoslavia that reported 7.6%, 37 and 12.6%, 38 respectively. However, studies conducted in Brazil and Spain have reported that the prevalence of MRH among young women was 69.2% and 45.14%, 39,40 respectively. The evidence highlights that MRH was not assessed by a neurologist in this study and was self-reported by the participants, which might have increased the magnitude of MRH in this study.…”
Section: Discussionmentioning
confidence: 97%
“…General population VM prevalence is estimated between 1 and 3% (Paz‐Tamayo et al, 2020), whilst MM affects about 20‐25% of female migraineurs (Vetvik & MacGregor, 2021). Potential reasons for the >50% prevalence rates in the studies within the current review include financial incentivization and a self‐report survey via Facebook (Abouzari et al, 2020), and in Tavares et al, 2021; inclusion of females at the peak of reproductive age (18–28 years old). A higher menstrual migraine frequency has also been demonstrated in women living together (Ferreira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%